PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA PT. MATAHARI PUTERA PRIMA (HYPERMART) - Rafida Khairani; Celsi ApriWenny Siregar; Ribka Hartati Hutabalian; Ika Irawati Karolina (JURNAL MANAJEMEN, 2019)
This research was conducted to test and analyze the effect of price and service quality on consumer satisfaction at PT. Matahari Putera Prima (Hypermart) both partially and simultaneously. This study used a quantitative approach. The population of this study was the consumers of PT Matahari Putera Prima. The sampling technique used the Slovin formula so that the samples obtained for the regression test were 100 respondents. The results showed that simultaneously the price and service quality had a positive and significant effect on customer satisfaction at PT. Matahari Putera Prima (Hypermart). Partially, price and service quality have a positive and significant effect on customer satisfaction at PT. Matahari Putera Prima (Hypermart).